Polarization-modulated random fiber laser. (22nd March 2016) - Wu, Han; Wang, Zinan; He, Qiheng; Fan, Mengqiu; Li, Yunqi; Sun, Wei; Zhang, Li; Li, Yi; Rao, Yunjiang
Abstract: In this letter, we propose and experimentally demonstrate a polarization-modulated random fiber laser (RFL) for the first time. It is found that the output power of the half-opened RFL with polarized pumping is sensitive to the state of polarization (SOP) of the Stokes light in a fiber loop acting as a mirror. By inserting a polarization switch (PSW) in the loop mirror, the state of the random lasing can be switched between on/off states, thus such a polarization-modulated RFL can generate pulsed output with high extinction ratio.